1981
DOI: 10.1071/zo9810671
|View full text |Cite
|
Sign up to set email alerts
|

Longevity, Resource Utilization and Larval Preferences in Drosophila: Inter- and Intraspecific Variation.

Abstract: On the basis of life-span, the threshold ranking at which ethanol and acetic acid ceased to be resources and became stresses for 3 sympatric, cosmopolitan Drosophila species was: D. melanogaster Mg. > D. simulans Sturt. > D. immigrans Sturt. The threshold ranking between larval attraction and avoidance followed the same sequence. An Adh-null mutant of D. melanogaster utilised ethanol to an extremely low threshold, while acetic acid was utilised to a threshold close to that of the D. melanogaster populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

1984
1984
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…At low concentration, acetic acid is, like ethanol, used as a resource (11,12). We found that ethanol adaptation, due to directional selection, was accompanied by an increase ofacetic acid tolerance (Fig.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…At low concentration, acetic acid is, like ethanol, used as a resource (11,12). We found that ethanol adaptation, due to directional selection, was accompanied by an increase ofacetic acid tolerance (Fig.…”
Section: Discussionmentioning
confidence: 83%
“…Experimental data suggest that lipid synthesis could be more important in larvae (25,(28)(29)(30), whereas energy production would be more important in adults, especially in laboratory tests in which survival duration is measured (11,31,32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…D. simulans usually avoids entering buildings because it tends to be photopositive Watanabe 1978), ethanol sensitive (McKenzie andParsons 1972) and is not attracted by man-made construction (David 1979;Fuyama and Watada 1981). Differing food preferences including the degree of resistance to ethanol may contribute to the coexistence of the both species with reduced competition in nature (Kawanishi and Lee 1978;Parsons and Spence 1981). However, the most important factor affecting the expansion of D, simulans in nature will be the climate or temperature.…”
Section: Discussionmentioning
confidence: 99%
“…For a coherent evolutionary analysis of species and populations, an integration of genetics at the levels of populations and ecology is needed (Ushakumari and Ranganath 1986b). Drosophila has been used as a representative system to understand genetic basis of ecological differentiation (Parsons and Spence 1981;Powell and Andjelkovic 1983;Taylor and Condra 1983;Ramachandra and Ranganath 1986). Parsons and Spence (1981) have shown resource utilization divergence among 6 closely related Drosophila species of melanoqaster subgroup in the utilization of ethanol and acetic acid as energy sources.…”
Section: Ecogenetic Divergencementioning
confidence: 99%